2014
DOI: 10.1002/jssc.201400662
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a hydrophilic interaction liquid chromatography with tandem mass spectrometry method for the simultaneous detection and quantification of etilefrine and oxilofrine in equine blood plasma and urine

Abstract: A sensitive hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry method was developed and validated for the simultaneous detection and quantification of etilefrine and oxilofrine in equine blood plasma and urine. The method is highly sensitive and specific with good precision and accuracy. In plasma the limit of detection and limit of quantification are 0.03 and 0.1 ng/mL, respectively, for both analytes. In urine the limit of detection and limit of quantification are 0.3 and 1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…HILIC may help solve this problem because compared with RPLC, polar and hydrophilic analytes are more greatly retained on an HILIC column but few studies exist describing quantification of hydrophilic target analytes like morphine and codeine and their glucuronide [41], cathinone-designer drugs (11 chemicals) [77], etilefrine and oxilofrine [78], ephedrines [79,51] and narcotics [80]. The few studies reported suggest that HILIC requires simple sample preparation, offers good sensitivity and robustness and only requires adequate column equilibration and precondition time.…”
Section: Specificity Of Interest Moleculesmentioning
confidence: 99%
“…HILIC may help solve this problem because compared with RPLC, polar and hydrophilic analytes are more greatly retained on an HILIC column but few studies exist describing quantification of hydrophilic target analytes like morphine and codeine and their glucuronide [41], cathinone-designer drugs (11 chemicals) [77], etilefrine and oxilofrine [78], ephedrines [79,51] and narcotics [80]. The few studies reported suggest that HILIC requires simple sample preparation, offers good sensitivity and robustness and only requires adequate column equilibration and precondition time.…”
Section: Specificity Of Interest Moleculesmentioning
confidence: 99%
“…Furthermore, reliable HILIC method was used for the detection of therapeutic agent and/or their metabolites in more than one matrix . For example, antihypertensive drug etilefrine and oxilofrine in equine blood plasma and urine were determined with a HALO HILIC column (50 × 2.1 mm id, particle size 2.7 μm) coupled with ESI‐MS/MS detector, the method showed relatively low LOD (≤ 0.1 ng/mL) and LOQ (≤ 1.0 ng/mL) in both matrices .…”
Section: Chemical Drug Analysismentioning
confidence: 99%
“…Growing the ratio of these deaths were correlated with a prescription drug overdose. The various analytical techniques are used to detect the ET‐HCl include spectrophotometry, flow injection chemiluminescence, proton magnetic resonance spectroscopy, HPLC, and GC–MS . The numerous analytical methods have been used to detect PC in different matrices including chromatography, spectrophotometry, titrimetry, chemiluminescent .…”
Section: Introductionmentioning
confidence: 99%